Hubungan Tekanan Darah dan Lama Menderita dengan Laju Filtrasi Glomerulus Pasien Hipertensi - Adiba Zaza Salsabila; Dwi Retno Sulistyaningsih; Indah sri wahyuningsih (Journal of Medical Practice and Research, 2025)
Hypertension is a prevalent chronic health condition and a major risk factor for cardiovascular disease and chronic kidney disease. Persistent elevation of blood pressure can lead to progressive damage to blood vessels and glomeruli through hemodynamic and structural mechanisms, ultimately resulting in a decline in the glomerular filtration rate (GFR). In addition to blood pressure levels, the duration of hypertension plays a crucial role in determining the extent of renal damage over time. This study aimed to analyze the relationship between blood pressure, duration of hypertension, and GFR. A quantitative study with a cross-sectional design was conducted involving 103 patients with hypertension. Data were obtained from medical records, including systolic and diastolic blood pressure, duration of hypertension, and GFR values, and were analyzed using Spearman’s correlation test. The results showed that systolic blood pressure was significantly associated with GFR (p < 0.05), with a weak negative correlation, while diastolic blood pressure showed no significant association. The duration of hypertension was also significantly associated with GFR. In conclusion, systolic blood pressure and the duration of hypertension influence renal filtration function, highlighting the importance of regular monitoring of blood pressure and GFR to prevent further kidney damage.